Comments on section 2: Significant contributions to research on learning and assessment - Treagust, David (Springer Singapore, 2016)
© Springer Science+Business Media Singapore 2016. As has been discussed throughout this volume, the vision and direction of the National Science Council has resulted in science educators in Taiwan being very prominent among the world’s science educators in the international literature and at international meetings and conferences. As an example, I have recently returned from the annual conference of the Australasian Science Education Research Association held in Melbourne, Australia. At this conference, among the international scholars in attendance were several from Taiwan who presented their work as an oral session or a poster. The research presented in every case that I attended was of high quality and was shown with posters; these could serve as good examples of successful poster presentations and layouts. Consequently, my experience from the first week of July 2014 in Melbourne was consistent with the quality of the research work presented in the four chapters in this section. Over the past 15–20 years, Taiwanese science education researchers have contributed substantially to the extant published literature and discussions, and debates at international conferences. These publications generally utilize rigorous methodologies and explain findings within the theoretical framework presented.